Mass loading optimization for ethylene glycol oxidation at different potential regions - Sun, Shengnan (2023)
Designing and fabricating the electrocatalysts is attracting more and more attention in recent years due to a global interest in developing techniques for electrochemical energy conversion and storage, as well as elelectro-synthesis of valuable chemicals. The activity is one of the key performance parameters for electrocatalysts, while the observed activity can be affected by mass loading of electrocatalysts. Here, we take cobalt oxide (Co3O4)/graphite paper electrode (Co3O4/GPE) as a model electrode to demonstrate how the mass loading of Co3O4 catalyst influences ethylene glycol (EG) oxidation in alkaline (KOH) by cyclic votammetry (CV) and chronopentiometry (CP) approaches. Analyses from redox peaks and double layer capacitances reveal that increasing the mass loading provided more electrochemical active sites. Increasing loading made a positive contribution to EG oxidation at the low oxidation potential, while less significant improvement at the high oxidation potential. The results will provide some insight for optimzing the mass loading of electrocatalysts for electrocatalysis of small organic molecules.